2017
DOI: 10.1111/1911-3846.12296
|View full text |Cite
|
Sign up to set email alerts
|

Are Related Party Transactions Red Flags?

Abstract: This study investigates whether or not related party transactions serve as "red flags" that warn of potential financial misstatement. We hand-collect related party transactions for S&P 1500 firms in 2001, 2004, and 2007 and find a positive correlation between these transactions and future restatements, suggesting restatements are more likely when a firm engages in related party transactions. The association is concentrated among transactions that appear to reflect "tone at the top" rather than arguably more n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(144 citation statements)
references
References 36 publications
8
123
1
12
Order By: Relevance
“…The Kohlbeck and Mayhew () study finds that simple RP_TONE s are red flags for poor accounting quality associated with lower audit fees. The authors develop a model to explain these observations, suggesting that RP_TONE is associated with poor “tone at the top” and that this leads the management to negotiate for lower‐quality audits to minimize monitoring costs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kohlbeck and Mayhew () study finds that simple RP_TONE s are red flags for poor accounting quality associated with lower audit fees. The authors develop a model to explain these observations, suggesting that RP_TONE is associated with poor “tone at the top” and that this leads the management to negotiate for lower‐quality audits to minimize monitoring costs.…”
Section: Resultsmentioning
confidence: 99%
“…In their paper, Kohlbeck and Mayhew () (hereafter KM), analyze hand‐collected data for listed U.S. S&P 1500 firms for 2001, 2004 and 2007 to demonstrate that certain types of related party transactions (RPTs) are associated with a higher likelihood of financial restatement and, surprisingly, with a lower audit fee . The authors present two main findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of this abuse could lead to a reduction in shareholder wealth (tunneling transactions), yielding a virtual increase in the resources of the corporation or finally towards producing misleading statements (earnings management). Furthermore, some studies (Gordon et al, 2004;Kohlbeck & Mayhew, 2005) conclude that weak CG leads to a larger number of RPTs. Several studies have confirmed the use of earnings management by large numbers of listed companies in order to achieve particular levels of return on equity (ROE) (Chen & Yuan, 2004;Liu & Lu, 2007).…”
Section: Literature Review Of Rptsmentioning
confidence: 99%
“…Although the theories are opposed, Kohlbeck and Mayhew (2005) suggest that the potential benefit or detriment depends on the parties involved in the transaction or the type of RPTs conducted.…”
Section: Literature Review Of Rptsmentioning
confidence: 99%